Pelatihan Peningkatan Omset Pendapatan Industri Rumahan Nasi Krawu Di Kabupaten Gresik - Titus Kristanto; Nanang Fakhrur Rozi; Eka Cahya Muliawati; Rachman Arief; Syaiful Hidayat; Halimatus Sadiyah (Jurnal Pengabdian Masyarakat Khatulistiwa, 2020)
In the millennial era 4.0, the growth of the home industry is growing more rapidly with the development of information technology, thus making needs increase and create new business opportunities. One of the new business opportunities is the krawu rice business. Krawu rice is a typical food from Gresik Regency. The krawu rice home industry is a partner of a community service activity named Nasi Krawu Buk Tiban. The problem that occurs in the community service partners is the marketing of krawu rice that is still around the Nasi Krawu Buk Tiban environment and marketing through the internet media. The method used is to provide training in the form of online media marketing and social media assistance. The result of community service activities can increase krawu rice revenue turnover, can operate and promote krawu rice marketing through online media and social media.